Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.5296/emsd.v8i1.14315
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Quality in Steel Making Industries

Abstract: Steel making industry is one of the major contributors to the global environmental catastrophes including climate change, photochemical smog and depletion of the ozone layer. Emissions from steel making process result in health impacts on workers and the neighboring communities. This study aimed to investigate indoor air quality in a steel making industry in Saudi Arabia. Indicative pollutants, SO2, NOx, CO, CO2, O3, PM10 and PM2.5 were measured at eight locations across the factory. The obtained results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The conclusion of research concerning IAQ in steel rolling industry, performed by Al-Zboon et al [8], is that PM 10 and PM 2.5 exceeded the international standards at most of the measuring points. Furthermore, within the study related to IAQ in steel making industry, Al-Zboon and Forton [9] reported extremely high concentrations of PM 10 and PM 2.5 in the indoor air. According to research performed by Nazli et al [10], PM 2.5 is one of the most prominent pollutants that causes workers' complaints in the food industry.…”
Section: Introductionmentioning
confidence: 93%
“…The conclusion of research concerning IAQ in steel rolling industry, performed by Al-Zboon et al [8], is that PM 10 and PM 2.5 exceeded the international standards at most of the measuring points. Furthermore, within the study related to IAQ in steel making industry, Al-Zboon and Forton [9] reported extremely high concentrations of PM 10 and PM 2.5 in the indoor air. According to research performed by Nazli et al [10], PM 2.5 is one of the most prominent pollutants that causes workers' complaints in the food industry.…”
Section: Introductionmentioning
confidence: 93%
“…Some researchers have reported the levels of PM 10 and PM 2.5 in the cement processes. A study reported the levels of PM 10-2.5 in cement mill (2.15, 0.03 mg m −3 , respectively), loading area (0.03, 0.02 mg m −3 , respectively), and crusher (0.25, 0.07 mg m −3 , respectively) [41]. Another researcher reported the level of PM 10-2.5 in the cement processes included cement mill (0.59, 0.87 mg m −3 , respectively), packing (0.51, 0.50 mg m −3 , respectively), and crusher (1.55, 1.80 mg m −3 , respectively) [42].…”
Section: Wide Range Distribution Of Particulate Matters In the Cement Grinding Processmentioning
confidence: 99%
“…The initial symptoms of VOCs inhalation include discomfort of throat and nose, dyspnea headache, irritation of skin, fatigue, and dizziness. High dosage may lead to loss of coordination, and damage to liver, kidney, and the central nervous system (EPA, 2017;Al-Zboon and Forton, 2019). Since there are thousands of VOCs, no standards have been set, while there are standards for some compounds which health risks such as formaldehyde.…”
Section: Effect Of Vocsmentioning
confidence: 99%